Reserve of the Possible and the Existential Minimum: limitations to the realization of fundamental rights (Research, Society and Development, 2022)
The present work deals with the theme of the existential minimum and the reserve of the possible in face of the budgetary limitations of the State. Issues related to existing clashes between fundamental social rights and State budget limitations are addressed, analyzing the current debate about this issue in the Brazilian scenario. The study of this theme is relevant because the existential minimum is a set of fundamental rights essential to the existence of human dignity, while the reservation of the possible seeks to limit the realization of such rights, taking into account the factual limitation, legality and reasonableness. In this sense, social rights, despite being provided for in our Federal Constitution of 1988, face limitations as to their effectiveness. The obstacles faced in relation to the matter are present as a result of the existing neglect regarding the realization of social rights, since the existing public policies are insufficient to meet the needs of the Brazilian population. The present work has as objective an investigation, which seeks to verify if the absence of financial resources of the State, in some way, is limited by the reserve of the possible, compromising the minimum necessary for the dignified existence of the human person. The methodology used consists of jurisprudential and bibliographic research, with a descriptive and qualitative approach, with the purpose of formative evaluation. It is concluded, therefore, that when the reserve of the possible is used only as a limitation and not as an obstacle to the existential minimum, it is fully possible for both principles to coexist peacefully.